PATTERN OF RHEUMATIC DISEASES IN THE DIVISION OF RHEUMATOLOGY, DR. SOETOMO GENERAL ACADEMIC HOSPITAL, SURABAYA, INDONESIA, BETWEEN NOVEMBER 2021 AND MARCH 2022 - Afifur Rafi Hilmi Aziz; Yuliasih; Imam Subadi (Universitas Airlangga, Surabaya, Indonesia, 2023)
Highlights: Rheumatic diseases, like many others, are often misdiagnosed and treated late in life, resulting in the increase of rheumatic diseases incidence. Gender, age, level of education, and occupation all play crucial roles in the onset of rheumatic disorders. Abstract Background: The epidemiology of rheumatic diseases plays an important role in the spread of rheumatic diseases worldwide. Epidemiology data of rheumatology diseases in Dr. Soetomo General Academic Hospital remains unclear as there are some problems such as rheumatic drug depletion and imperfect medical recording. Â Objective: This study aimed to analyze the pattern of rheumatic diseases at the Division of Rheumatology, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Â Material and Method: This prospective descriptive study used secondary data from medical records between November 2021 and March 2022 at the Division of Rheumatology, Dr. Soetomo General Academic Hospital. The variables of this study were gender, age, occupation, education level, disease duration, and clinical manifestations. Results: Secondary data was provided by 109 patients in this study. Gender was dominated by women as much as 96 (88%), age was dominated by age groups 26-35 years and 46-55 years, each as much as 26 (23.8%), educational level was dominated by senior high school as much as 24 (22%), and employment was dominated by housewives as much as 39 (35.7%) in the Divison of Rheumatology, Dr. Soetomo General Academic Hospital, Surabaya, Indonesia. Based on disease incidence, 42 patients (38.5%) had systemic lupus erythematosus, and 38 patients (34.8%) had ankylosing spondylitis. Conclusion: Rheumatology patients at Dr. Soetomo General Academic Hospital Surabaya are predominantly female, aged 26-55, with senior high school education. The diseases mostly affect housewives and have a higher frequency of systemic lupus erythematosus and ankylosing spondylitis.